IMPLEMENTASI PEMBERIAN PRESKRIPTIF DALAM PENILAIAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XII IPB SMA NEGERI 1 PETANG TAHUN PELAJARAN 2018/2019 - Kuta, I Gusti Agung Gede (LPPM IKIP PGRI Bali, 2020)
The purpose of this study was to determine the implementation of prescriptive giving in assessments to improve mathematics learning outcomes of students of class XII IPB SMAN 1 Petang 2018/2019 academic year. This research is a classroom action research whose implementation was designed in two cycles. The design for each cycle consists of four stages: planning, implementation, observation / evaluation, and reflection. The subjects of this class action research were students of class XII IPB Odd Semester at SMAN 1 Petang 2018/2019 Academic Year consisting of 27 students. Data on student learning outcomes are collected collected and descriptively. The results of this study indicate that, the implementation of prescriptive giving in assessment can improve mathematics learning outcomes of students of class XII IPB SMAN 1 Petang. From the analysis obtained classical learning completeness in the first cycle was only 62.96%, and in the second cycle to 81.48%, so there was an increase of 18.52%. Likewise with the average and absorption has increased by 3.40% from 76.73% in the first cycle to 80.13% in the second cycle. This means that prescriptive giving in assessment can improve mathematics learning outcomes of students of class XII IPB SMAN 1 Petang in odd semester 2018/2019.